COMPETENCY BASED PAY SYSTEM DESIGN AT KURSUS INDONESIA - Rahma Dinda Dwi Ptri; Aurik Gustomo (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
In today globalization era, competition among business is getting tighter, and it is not only about attracting customers but also attracting and retaining human capital. Kursus Indonesia have a difficulty in attract and retain their employee, and founded that their current compensation not yet satisfying their employees. This study aims to find the root cause of Kursus Indonesia’s compensation problem, design a strategic compensation system and compare the new compensation proposed salary with benchmark salary. This study used qualitative research method and the data used are primary data (interview and observation) and secondary data (literature study). To process the data gained, this study used descriptive analysis with business situation analysis and current reality tree root cause analysis, job analysis and point method job evaluation. This study found that (1) The root cause of Kursus Indonesia’s compensation problem is no alignment between the current compensation strategy with company’s business strategy; (2) Design a Competency Based Pay system is a suitable approach to solve Kursus Indonesia’s compensation problem; (3) This solution propose some improvent in Kursus Indonesia’s employee salary by using Lead Pay Policy that pay above benchmark salary.Keywords: Attract and Retain, Compensation, Competency Based Pay,Competition, Salary